Neuro-Ophthalmological Warning Signs in Intracranial Neoplasms: Clinical Patterns for Early Detection and Visual Preservation - Patricia Equilea Veizaga; Alejandra Mendoza Ortiz; Natalia Restrepo Hinestrosa; Patricio Sánchez de Ovando González; Mariana Lineth Orozco Ricardo; Mariana Ramírez García; Jorge Angel Velasco Espinal; Alexa Fernanda Uriostegui Navarro (International Science Journal, 2026)
Neuro-ophthalmological manifestations may represent the first clinically detectable sign of intracranial neoplasms, particularly when tumors involve the optic nerves, optic chiasm, sellar and parasellar regions, cranial nerves, skull base, brainstem, or structures associated with intracranial pressure. This study analyzed the main visual and ocular manifestations associated with intracranial tumors and their potential value for early diagnosis through a descriptive and analytical review of the scientific literature. Evidence concerning pituitary macroadenomas, meningiomas, optic pathway gliomas, craniopharyngiomas, and other intracranial neoplasms was examined, integrating clinical findings with automated perimetry, funduscopic examination, optical coherence tomography, and magnetic resonance imaging. The reviewed data showed a predominance of afferent visual abnormalities, particularly progressive visual loss, transient visual obscurations, visual-field defects, optic-disc changes, and optic neuropathy. Pituitary macroadenomas and meningiomas represented the most frequent tumor groups in the analyzed clinical series. Anatomical localization was closely associated with the pattern of neuro-ophthalmological involvement: sellar and suprasellar lesions were predominantly related to visual-field abnormalities, while lesions affecting the anterior cranial base or optic apparatus frequently produced structural optic nerve changes. Optical coherence tomography demonstrated the ability to identify retinal ganglion cell abnormalities in a subset of patients with MRI-confirmed chiasmal compression despite normal conventional visual fields, supporting the complementary role of structural assessment in early disease. Diagnostic intervals varied considerably, ranging from days to several years, and a substantial proportion of patients experienced visual symptoms for more than six months before definitive tumor identification. These findings indicate that persistent, progressive, unexplained, or anatomically suggestive visual abnormalities should raise suspicion of intracranial pathology. Integrating neuro-ophthalmological examination, functional testing, structural retinal assessment, and neuroimaging may shorten diagnostic delay, improve anatomical localization, facilitate timely multidisciplinary referral, and increase the probability of preserving visual function before irreversible axonal damage develops.